¡De primaria a secundaria, he ahí el problema! - Villalobos H., Teresita (Revista Electrónica Educare, 2004)
This article deals with the problems students face in their transition from primary to secondary school. The paper analyses a series of comments made by 7-11 grade students of the Costa Rican educational system in relation to the experiences they are having or had during the process and to their opinions about their teachers.A proposal to diminish adaptation problems faced by 7th grade students is also presented. What is suggested is that the social and teaching changes that occur at this level should be interconnected in order to deal with them.